Modern Visual Aids in Classrooms: Enhancing EFL Vocabulary Retention Through Animated Videos in Satun, Thailand - Sofia Faradilla Suandi; Diani Syahputri (Journal of Practice Learning and Educational Development, 2026)
This study aims to investigate the effectiveness of animated videos as modern visual aids in improving vocabulary retention among ninth-grade EFL students at Thammasat Wittaya School, Satun, Thailand. This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model consisting of planning, action, observation, and reflection stages conducted in two cycles. The participants were 20 ninth-grade students. Data were collected through vocabulary tests and classroom observations. The findings showed that students’ vocabulary retention improved from 65% in Cycle I to 71% in Cycle II. Student activity also increased from 62% to 78%, while teacher activity improved from 70% to 88%. The study concludes that animated videos effectively improved students’ vocabulary retention, classroom participation, and engagement during EFL learning activities. Therefore, animated videos are recommended as effective instructional media for vocabulary learning in EFL classrooms.